Translation, Cultural Adaptation, and Reproducibility of the Physical Activity Readiness Questionnaire for Everyone (PAR-Q+): The Brazilian Portuguese Version - Schwartz, Juliano; Oh, Paul; Takito, Monica Y.; Saunders, Bryan; Dolan, Eimear; Franchini, Emerson; Rhodes, Ryan E.; Bredin, Shannon S. D.; Coelho, Josye P.; dos Santos, Pedro; Mazzuco, Melina; Warburton, Darren E. R. (Frontiers in Cardiovascular Medicine, 2021)
Background: The Physical Activity Readiness Questionnaire for Everyone (PAR-Q+) is the international standard for pre-participation risk stratification and screening. In order to provide a practical and valid screening tool to facilitate safe engagement in physical activity and fitness assessments for the Brazilian population, this study aimed to translate, culturally adapt, and verify the reproducibility of the evidence-based PAR-Q+ to the Brazilian Portuguese language. Method: Initially, the document was translated by two independent translators, before Brazilian experts in health and physical activity evaluated the translations and produced a common initial version. Next, two English native speakers, fluent in Brazilian Portuguese and accustomed to the local culture, back-translated the questionnaire. These back translations were assessed by the organization in charge of the PAR-Q+, then a final Brazilian version was approved. A total of 493 Brazilians between 5 and 93 yr (39.9 ± 25.4 yr), 59% female, with varying levels of health and physical activity, completed the questionnaire twice, in person or online, 1–2 weeks apart. Cronbach's alpha was used to calculate the internal consistency of all items of the questionnaire, and the Kappa statistic was used to assess the individual reproducibility of each item of the document. Additionally, the intraclass correlation coefficient and its 95% confidence interval (CI) were used to verify the general reproducibility (reliability) of the translated version. Results: The Brazilian version had an excellent internal consistency (0.993), with an almost perfect agreement in 93.8% of the questions, and a substantial agreement in the other 6.2%. The translated version also had a good to excellent total reproducibility (0.901, 95% CI: 0.887–0.914). Conclusion: The results show this translation is a valid and reliable screening tool, which may facilitate a larger number of Brazilians to start or increase physical activity participation in a safe manner.